Peningkatan Mutu Pembelajaran Melalui Pengembangan Sarana dan Prasarana - Umar, Sinardi; Senang, Senang; Sunardi, Sunardi (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
Education is the main pillar in the development of society and the country. One effort to improve the quality of learning is by developing educational institutions' facilities and infrastructure. This research focuses on improving the quality of learning at MTs H. Agus Salim Gudo through efforts to develop facilities and infrastructure. The research method used is a case study with a qualitative approach. Data was collected through interviews, observation, and analysis of related documents. The research results show that the development of facilities and infrastructure at MTs H. Agus Salim Gudo has positively impacted the quality of learning. Developing comfortable classrooms equipped with modern learning facilities creates a conducive learning environment. The construction of libraries equipped with relevant book collections also contributes positively to improving the quality of learning. Besides that, using interactive learning software and adequate computer facilities helps increase student engagement and enrich learning methods. Student involvement in extracurricular activities related to sports and the arts provides additional valuable experience in the learning process. This research provides recommendations for other educational institutions to pay attention to the development of facilities and infrastructure as an effective strategy for improving the quality of learning. Continuous improvement of learning facilities can be a long-term investment to achieve better educational goals